Narrative literature review: Health, activity and participation issues for women following traumatic brain injury. Issue 19 (11th September 2018) - O'Reilly, Kate; Wilson, Nathan; Peters, Kath
Abstract: Objective: This narrative review will draw attention to the current limitations within the literature related to women following traumatic brain injury in order to stimulate discussion and inform future directions for research. Background: There is a wide-ranging body of research about traumatic brain injury with the higher incidence of brain injury among males reflected in this body of work. As a result, the specific gendered issues facing women with traumatic brain injury are not as well understood. Method: A search of electronic databases was conducted using the terms "traumatic brain injury", "brain injury", "women", "participation", "concussion" and "outcomes". Results : The 36 papers revealed the following five themes (1) Relationships and life satisfaction; (2) Perception of self and body image; (3) Meaningful occupation; (4) Sexuality and sexual health; and (5) Physical function. Conclusions: Without research, which focuses specifically on the experience of women and girls with traumatic brain injury there is a risk that clinical care, policy development and advocacy services will not effectively accommodate them. Implications for rehabilitation: Exploring the gendered issues women may experience following traumatic brain injury will enhance clinicians understanding of the unique challenges they face. Such information has the potential to guide future directions for research, policy, and practice. Screening women for hormonal imbalances such as hypopituitarism following traumatic brain injury is recommended as this may assist clinicians in addressing the far reaching implications in regard to disability, quality of life and mood. The growing literature regarding the cumulative effect of repeat concussions following domestic violence and women's increased risk of sport-related concussion may assist clinicians in advocating for appropriate rehabilitation and community support services.